Göran Greider, Ingen kommer undan Olof Palme (Stockholm: Ordfront, 2011) - Monica Quirico (Nordicum-Mediterraneum, 2012)
In 2011 within the Swedish labour movement many activists dissatisfied with the Social Democratic Party (SAP) – who in 2010 suffered from the second electoral defeat in succession and fell into a never-ending crisis – turned to the legacy of Olof Palme (whose XXV death anniversary was celebrated on February, 28) as a flag of the true Social Democratic tradition, to which it is urgent to come back before the centre-right government achieves a full “paradigm shift”, deregulating further the labour market and privatizing the Welfare State.